Comic Strip Media Design for Arabic Language Learning in Fourth Grade Elementary School - Anisa Ocktavia; Hani`atul Mabruroh; Agus Yasin (Al Maghazi : Arabic Language in Higher Education, 2025)
Background of this study stems from the lack of visual-based Arabic learning media in elementary schools, causing student disengagement. Aims and scope of the paper are to design and evaluate hand-drawn comic strips for fourth-grade students using the ADDIE model to provide a more interactive learning experience. This Research and Development (R&D) study aims to design and evaluate comic strip media for teaching Arabic at MI Al-Huda. The development was driven by students’ need for concrete visual learning tools. The ADDIE model was applied through five stages: Analyze, Design, Development, Implementation, and Evaluation, focusing on the theme “My Job.” Data were gathered using rating scales involving subject matter experts, media experts, a classroom teacher, and students. Expert validation results revealed that the Aiken’s V index ranged from 0.85 to 1.00 for subject matter experts and 0.60 to 1.00 for media experts, indicating high validity levels. Furthermore, the teacher and students provided highly positive feedback, with mean scores of 4.60 and 4.90, categorized as "Very Good." These findings suggest that the comic strip media is appropriate for classroom implementation, effectively enhancing students’ understanding and engagement. Moreover, the media contributes to a more enjoyable Arabic learning experience for elementary-level learners. Scientific contributions of this study include providing an innovative pedagogical model for Arabic instruction through hand-drawn visual narratives that simplify abstract linguistic concepts for young learners, and suggestions for future research involve conducting large-scale experimental studies to measure the long-term impact on students' vocabulary retention.